Understanding the Determinants of Hotel Consumer Trust : A Perspective Commitment-Trust Theory - Juliana, Juliana; Pramezwary, Amelda; Patricia, Veren; Josephine, Josephine; Lewinsky, Silvia; Putra, Hans Dhammika (IJOSMAS, 2021)
Hospitality services are significantly affected by the pandemic, inseparable from Bali's province, known as the highest contributor of tourism revenue in the affected country of Indonesia, where the occupancy rate of hotels in Bali is also decreasing. This investigation will analyze the impact of services, Communication reduction on Bali hotels' occupancy during the Covid-19 outbreak. The research objective is to develop a conceptual model of consumer trust by implementing health protocol services and setting low prices. The research method used is descriptive quantitative with questionnaire instruments that have been disseminated, then each answer is processed and analyzed with a statistical application, namely PLS-SEM. Determination of the sample using non-probability sampling with 100 respondents. The findings also show that the influence on services, especially in the current health protocol, becomes significant in the hospitality service industry. The low Communications also directly affect tourists to choose hotels in the middle of a pandemic like this. Keywords: Health protocol services, communication,, consumer trust